1991
DOI: 10.1111/j.1365-2362.1991.tb01402.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin receptor antagonist loxiglumide modulates plasma levels of gastro‐entero‐pancreatic hormones in man Feedback control of cholecystokinin and gastrin secretion

Abstract: The effect of the potent specific cholecystokinin (CCK) receptor antagonist loxiglumide on meal-stimulated plasma concentrations of CCK, gastrin, pancreatic polypeptide (PP), neurotensin, glucose-dependent insulinotropic polypeptide (GIP), insulin and C peptide was investigated in a placebo-controlled study in 10 healthy male volunteers. Intravenous infusion of loxiglumide (10 mg kg-1 h-1) significantly augmented integrated incremental IR-CCK levels 7.3-fold after stimulation by a standard breakfast (504 +/- 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 49 publications
2
12
1
Order By: Relevance
“…Although our data are in contrast with a role of CCK as an enterogastrone, it can not be excluded that CCK acts locally as a neurotransmitter or neuromodulator to inhibit gastric acid secretion, since specific cholecystokinin recep tor antagonists augment gastric acid secretion in previous experiments [36][37][38][39][40][41].…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Although our data are in contrast with a role of CCK as an enterogastrone, it can not be excluded that CCK acts locally as a neurotransmitter or neuromodulator to inhibit gastric acid secretion, since specific cholecystokinin recep tor antagonists augment gastric acid secretion in previous experiments [36][37][38][39][40][41].…”
Section: Discussioncontrasting
confidence: 85%
“…Several possibil ities have been suggested [7,[9][10][11][12]34]. Of old, one of the most important enterogastrone candidates is CCK [7], In previous studies, infusion of high, probably supraphysiological, doses of CCK inhibited gastric acid secretion [35], Recent studies with CCK receptor antagonists also support an inhibitory effect of endogenous CCK on gastric acid secretion, since specific type A CCK-receptor antagonists augmented basal as well as stimulated gastric acid output [36][37][38][39][40][41]. However, in the present study infusion of CCK did not inhibit gastric acid secretion, and medium chain triglycerides were able to inhibit gastric acid secretion without concomitant release of CCK.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, this phenomenon was also seen in the basal interdigestive state and with bethanechol infusion. A feedback mechanism between duodenal bile secretion and CCK release could be operative, and inhibition of biliary secretion by loxiglumide would enhance CCK release [30].…”
Section: Cck-receptor Blockadementioning
confidence: 99%
“…It has been suggested that the inhibition of gastric acid secretion is also mediated at least in part by CCK (8)(9)(10)(18)(19)(20)(21)(22). uonsulfated gastrin-17 was Cambridge Research Biochemicals (Cheshire, United King dom).…”
Section: Introduction Materialsmentioning
confidence: 99%
“…This might be the reason for the absence of plasma CCK secretion and suppression of gastric acid secretion in response to sucrose polyester. CCK may be involved in the suppression of gastric acid secretion by intraduodenal fat (18)(19)(20)(21)(22), although we showed that suppres sion of acid secretion can be reached by medium-chain triacylglycerols without concomitant CCK release (39). The in crease of plasma CCK in response to digestible fat was TABLE 1 Gastric acid output in (he stomach before gastrin infusion (basal), during gastrin infusion, and during intraduodenal perfusion of sucrose polyester (SPE), digestible fat, or saline in eight volunteers; intravenous gastrin infusion was continued during the intraduodenal perfusion of fat7 …”
mentioning
confidence: 99%